Pengaruh Kualitas Pelayanan Dan Lingkungan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Petong Cafe & Art House Andonosari Kabupaten Pasuruan) - Selfi Apriliya; Abdul Kodir Djaelani; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine and analyze the effect of service quality and the environment on customer loyalty through customer satisfaction Petong Cafe & Art House. This research is a type of explanatory research, with a quantitative approach. The research method used is path analysis. The sampling technique used purposive sampling, the sample was obtained by 64 respondents. The results of this study indicate that partially all variables have a significant and positive effect. While the results of the intervening test showed that customer satisfaction was able to mediate the relationship between service quality and the environment on customer loyalty Petong Cafe & Art House. The interesting thing from this research can be seen from the answers of the highest respondents, namely the product menu presented by Petong Cafe & Art House in accordance with consumer expectations and the products and services give a positive impression to customers. Keywords: Service Quality, Environment, Customer Satisfaction, and Customer Loyalty